The Reception of Thomas Carlyle in Land Reform Movements in Australia and New Zealand, c. 1860–1914. (4th May 2022) - Jordan, Alexander
ABSTRACT: This article examines the ways in which the writings of the great Victorian man of letters Thomas Carlyle (1795–1881) were appropriated by land reformers in Australia and New Zealand. Carlyle argued that the land had been created by God for the benefit of the whole people, and that its possessors thus had a duty to put it to the best possible use. In this sense, work was the sole legitimate title to land. On these grounds, Carlyle was highly critical of the landowners of his era, whom he considered to be grossly remiss in their duties, living a life of idleness and luxury at the expense of their tenants. However, Carlyle did not go so far as to recommend the expropriation of the landlords, leaving open the possibility that they might still reform their behaviour. Ignoring this qualification, land reformers in Australia and New Zealand appropriated Carlyle's writings, extending his denunciations of the hereditary nobility of Britain to the capitalist sheep-farmers and 'squattocrats' of the Antipodes, as well as adducing Carlyle in support of their own proposals for radical reform.